2021
DOI: 10.21608/javs.2021.102235.1111
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Topically Applied Hyaluronic Acid on Skin Wound Healing in Rabbits

Abstract: This study aims to evaluate the effect of the topical application of hyaluronic acid cream 0.2% in the skin wound healing in rabbits. Thirty two healthy New Zealand adult male rabbits approximately at the same age and weight were involved in this study; all animals were anaesthetized using a 40 mg/kg ketamine and xylazine 4 mg/kg injection intramuscularly. The skin of the dorsum area of each rabbit was aseptically prepared and then two incisions (1cm in length) were made on the skin. Wounds were left without s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…Greater mean values for Aloe Vera gel treated specimens during all study time intervals, indicating the favorable action of Aloe Vera gel on wound epithelialization process, which can be rationalized by accelerated epithelial migration rate and higher number of fibroblasts; indicating the favorable action of Aloe Vera gel on wound epithelialization process, which can be rationalized by accelerated epithelial migration rate and higher number of fibroblasts, Bioactive elements of Aloe Vera gel, primarily polysaccharides such as acemannan, glucomannan,mannose-6-phosphate, glycoprotein, and lectins, activate it. Aloe Vera gel polysaccharides increase fibroblast proliferation as well as hyaluronic acid and hydroxyproline synthesis, which improves ECM and healing speed [28]. The epithelialization results in this study are consistent with those reported by Burusapat et al [29], who found a significantly greater epithelialization rate in Aloe Vera gel treated defects of split thickness skin graft donor sites.…”
Section: Discussionsupporting
confidence: 91%
“…Greater mean values for Aloe Vera gel treated specimens during all study time intervals, indicating the favorable action of Aloe Vera gel on wound epithelialization process, which can be rationalized by accelerated epithelial migration rate and higher number of fibroblasts; indicating the favorable action of Aloe Vera gel on wound epithelialization process, which can be rationalized by accelerated epithelial migration rate and higher number of fibroblasts, Bioactive elements of Aloe Vera gel, primarily polysaccharides such as acemannan, glucomannan,mannose-6-phosphate, glycoprotein, and lectins, activate it. Aloe Vera gel polysaccharides increase fibroblast proliferation as well as hyaluronic acid and hydroxyproline synthesis, which improves ECM and healing speed [28]. The epithelialization results in this study are consistent with those reported by Burusapat et al [29], who found a significantly greater epithelialization rate in Aloe Vera gel treated defects of split thickness skin graft donor sites.…”
Section: Discussionsupporting
confidence: 91%